Design and Synthesis of a Berberine Dimer: A Fluorescent Ligand with High Affinity towards G‐Quadruplexes. Issue 41 (13th August 2015) - Tera, Masayuki; Hirokawa, Takatsugu; Okabe, Sachiko; Sugahara, Kohtaro; Seimiya, Hiroyuki; Shimamoto, Keiko
Abstract G‐quadruplexes (G4) are thought to be important factors for telomerase inhibition and transcriptional/translational modulations. Bioinformatic analyses imply that the human genome and mRNA contain a multitude of G4‐forming sequences; however, their analysis requires selective and detectable ligands. Given that two molecules of fluorescent berberine (BBR) coordinate to telomeric G4 in their co‐crystals, we designed hydrocarbon‐linked BBR‐analogue dimers because we expected the alignment of two BBR chromophores would avoid Watson–Crick base pair intercalation, which should result in high selectivity towards G4. An alkene‐cis‐C2 BBR dimer showed the highest affinity (Kd ≤2.6 nM) and selectivity (ca. 900‐fold vs. duplex) towards G4. The intrinsic "light‐up" fluorescence properties of this BBR dimer, derived from its conformational switching by G4, allowed a selective visualization of various G4 in the gel without using additional bulky fluorescence dyes, which, combined with the observed lack of conformational change of the ligand, suggested future applications in in vitro detection systems.